Model Pengembangan Ilmu Politik di PTKIN: Pengalaman UIN Syarif Hidayatullah Jakarta - Sahid Gatara, Asep Abdul; Supriatna, Encup; Jamaludin , Adon N. (Jurnal Review Politik, 2018)
The development of political science at the State Islamic Religious College (PTKIN), especially the State Islamic University (UIN), tend to stand a lot on the paradigm and policy of scientific integration. Namely, the integration of religious sciences and general sciences. However, at the State Islamic University of Syarif Hidayatullah in Jakarta, through the Political Science Study Program of the Faculty of Social and Political Sciences, it did not only rest on scientific integration, but also an effort to synergize with the context of Islamness and Indonesianness. This research aims to describes and identifies political sicience of Islamness and Indonesianness as a model of the development of political science.